(untitled) (Indianapolis, Ind., 1995)
The guide covers the common features applicable to all Intranets in mini-tutorials, each of which can be completed in ten minutes or less. Timesaving tips, plain English definitions and "panic button" advice help users throughout the book. The text covers the two most popular Web browsers on the market: Netscape Navigator and Internet Explorer.
Keywords: Internet,Intranets (Computer networks),Mạng máy tính